Unnatural Amino Acid: 4-Aminopyrazolonyl Amino Acid Comprising Tri-Peptides Forms Organogel With Co-Solvent (EtOAc:Hexane) - Bollu, Amarnath; Giri, Prajnanandan; Dalabehera, Nihar Ranjan; Asmi, Asmita Rani; Sharma, Nagendra K. (Frontiers in Chemistry, 2022)
Ampyrone is an amino-functionalized heterocyclic pyrazolone derivative that possesses therapeutic values such as analgesic, anti-inflammatory, and antipyretics. The chemical structure of ampyrone exhibits excellent hydrogen bonding sites and is considered as the potential scaffold of supramolecular self-assembly. Recently this molecule has been derived into unnatural amino acids such as aminopyrazolone amino acid (APA) and their peptides. This report describes that one of its amino acids, O-alkylated ampyrone, containing hybrid (/β) peptides form organogel after sonication at 50-55 oC with 0.7-0.9% (w/v) in ethyl acetate: hexane (1:3). The formation/morphology of such organogels is studied by nuclear magnetic resonance (NMR), Fourier-transform infrared (FT-IR), circular dichroism (CD), scanning electron microscope (SEM), transmission electron microscopy (TEM), powder X-ray diffraction (Powder-XRD), and thermogravimetric analysis (TGA). Energy minimized conformation of APA-peptides reveal the possibility of intermolecular hydrogen bonding. Hence APA-Peptides are promisable peptidomimatices for the organogel-peptides.